2005
DOI: 10.1890/04-1540
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Species-Specific Neighborhood Effects in the Dipterocarpaceae of a Bornean Rain Forest

Abstract: Abstract. Although accumulating evidence indicates that local intraspecific densitydependent effects are not as rare in species-rich communities as previously suspected, there are still very few detailed and systematic neighborhood analyses of species-rich communities. Here, we provide such an analysis with the overall goal of quantifying the relative importance of inter-and intraspecific interaction strength in a primary, lowland dipterocarp forest located at Danum, Sabah, Malaysia. Using data on 10 abundant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
167
3
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(183 citation statements)
references
References 65 publications
7
167
3
5
Order By: Relevance
“…This is further supported by the fact that the proportion of neighbors that were conspecific declined significantly with focal tree size at all sites, particularly for sapling-sized neighbors. Numerous studies have reported strong conspecific negative density-dependent mortality in both tropical and temperate forests (Augspurger 1984, Terborgh et al 2008, Uriarte et al 2004a, Stoll and Newbery 2005, Chen et al 2010, Swamy and Terborgh 2010, Bai et al 2012, Comita et al 2014), particularly at early life stages (e.g., seedling and sapling stages; Zhu et al 2015). Our results are consistent with these other studies and demonstrate that such density-dependent mortality patterns are strong enough to structure forest composition.…”
Section: Effect Of Conspecific Neighbors On Local Compositionsupporting
confidence: 91%
“…This is further supported by the fact that the proportion of neighbors that were conspecific declined significantly with focal tree size at all sites, particularly for sapling-sized neighbors. Numerous studies have reported strong conspecific negative density-dependent mortality in both tropical and temperate forests (Augspurger 1984, Terborgh et al 2008, Uriarte et al 2004a, Stoll and Newbery 2005, Chen et al 2010, Swamy and Terborgh 2010, Bai et al 2012, Comita et al 2014), particularly at early life stages (e.g., seedling and sapling stages; Zhu et al 2015). Our results are consistent with these other studies and demonstrate that such density-dependent mortality patterns are strong enough to structure forest composition.…”
Section: Effect Of Conspecific Neighbors On Local Compositionsupporting
confidence: 91%
“…Note that this approach is based on a separation of scales. Several studies using individual-based analyses of local neighborhood effects on growth and survival have shown that direct plant-plant interactions may operate only at local plant neighborhoods Ͻ20-30 m, fading away at larger scales (12)(13)(14)25), and the parameter of dispersal kernels at BCI typically range at approximately Ͻ 40-50 m (2 2 is the mean square dispersal distance from parent to surviving offspring) (38). On the other hand, habitat conditions for trees, i.e., elevation, orientation, or soil nutrients, vary typically at larger scales along environmental gradients that are often related with topographical features such as slope and elevation (22,23,29,36).…”
Section: Definition and Estimation Of Isarmentioning
confidence: 99%
“…Studies investigating neighborhood effects on tree growth and survival showed that direct plant-plant interactions are strong at local plant neighborhoods (of, say, Ͻ30 m) but fade away at larger scales (12)(13)(14)25). We therefore expect strong departures from a neutral ISAR at local neighborhoods but mostly neutral ISARs at larger scales.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…It has been found that conspecifics are stronger competitors than heterospecifics (Stoll & Newbery 2005, Massey et al 2006, Pretzsch & Schütze 2009. This may be due to high competitive equivalence between individuals of the same species, whereas individuals of different species may use resources in a complementary, and thus more efficient way, and, thereby, reduce competition.…”
Section: Introductionmentioning
confidence: 99%